Patterns in Abundance and Seasonality of Insects in the Siruvani Forest of Western Ghats, Nilgiri Biosphere Reserve, Southern India - P. R. Arun; V. S. Vijayan (The Scientific World Journal)
The seasonal abundance patterns of insects inhabiting the understory vegetation of a mixed deciduous forest were examined with the help of the sweep-net sampling method. During the study period of 2 years, insects were sampled regularly from the understory vegetation of the three selected habitats (moist-deciduous, riverine, and teak plantation) of the mixed deciduous forest. Insect abundance was maximum in the moist-deciduous habitat and minimum in the teak plantation. Generally, insect abundance was the highest during the southwest monsoon in all habitats. The temporal pattern of fluctuations in the insect abundance followed more or less the same pattern in all the three habitats studied. The insect abundance of the understory vegetation varied among the habitats studied, while the pattern of seasonal fluctuations in insect abundance was comparable among habitats. Composition of the insect community also indicated prominent seasonal changes within habitats than interhabitat changes within a season.